2018
DOI: 10.3390/vaccines6040071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mixed Equine Influenza Vaccination on Correlate of Protection in Horses

Abstract: To evaluate the humoral immune response to mixed Equine Influenza vaccination, a common practice in the field, an experimental study was carried out on 42 unvaccinated thoroughbred weanling foals divided into six groups of seven. Three groups were vaccinated using a non-mixed protocol (Equilis® Prequenza-Te, Proteqflu-Te® or Calvenza-03®) and three other groups were vaccinated using a mix of the three vaccines mentioned previously. Each weanling underwent a primary EI vaccination schedule composed of two prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…27 Another study using PCPP for the intranasal delivery into mice of a formalin-inactivated bovine RSV (FI-bRSV) vaccine combined with immunostimulatory CpG oligodeoxynucleotides indicated that the FI-bRSV /CpG/PCPP co-formulation could induce virus neutralizing antibody responses in the serum, IFN-γ responses in the spleen and mucosal IgA responses in the lung, as well as protection from bRSV challenge. 28,29,30 These studies highlight the potential of such polyanionic adjuvants, which are also advantageous in terms of readiness of supply, easiness of formulation by simple mixing processes and quality control by using nuclear magnetic resonance (NMR) and high-performance size exclusion chromatography (HPSEC) techniques. 8 The aim of the present study was to confirm the adjuvant effect of SPA09 in a higher animal species closest to human, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study using PCPP for the intranasal delivery into mice of a formalin-inactivated bovine RSV (FI-bRSV) vaccine combined with immunostimulatory CpG oligodeoxynucleotides indicated that the FI-bRSV /CpG/PCPP co-formulation could induce virus neutralizing antibody responses in the serum, IFN-γ responses in the spleen and mucosal IgA responses in the lung, as well as protection from bRSV challenge. 28,29,30 These studies highlight the potential of such polyanionic adjuvants, which are also advantageous in terms of readiness of supply, easiness of formulation by simple mixing processes and quality control by using nuclear magnetic resonance (NMR) and high-performance size exclusion chromatography (HPSEC) techniques. 8 The aim of the present study was to confirm the adjuvant effect of SPA09 in a higher animal species closest to human, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While the vaccination schedule is similar between commercially available EIV vaccines, there were no recommendations for use of different EIV vaccines in the horse immunization schedule. However, the use of different commercial vaccines at different time points is a very common practice in the equine industry; this method is called the mixed regime [ 36 ]. Previous studies have already shown that the Calvenza-03 EIV/EHV ® vaccine induces the protective antibody titer immediately after immunization [ 29 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of different commercial vaccines at different time points is a very common practice in the equine industry; this method is called the mixed regime [ 36 ]. Previous studies have already shown that the Calvenza-03 EIV/EHV ® vaccine induces the protective antibody titer immediately after immunization [ 29 , 36 ]. No clear data is available regarding the long-term persistence of EIV-specific humoral antibody response.…”
Section: Discussionmentioning
confidence: 99%
“… 53 However, the role of individual components in generating these immune responses is unknown. At present, ISCOM technology has been approved only for veterinary vaccines; 54 however human clinical trials are currently ongoing for the development of melanoma vaccines. 55 …”
Section: Lipid-based Delivery Systemsmentioning
confidence: 99%